ԺԷ. դարի աշխարհաբար տպագիր գրքերը - Թամար Պողոսյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Данная статья посвящена изучению первых напечатанных на новоармянском языке в 17-ом веке книг - «Ремесло сосчитования» (Марсель, 1675), «Пояснение духовного псалмопевца Давида пророку» (Венециа, 1687), «Сокровища меры, веса, чисел и денег все гомира» (Амстердам, 1699). В статье было исследовано, в каких типографиях и при каких об стоятельствах были напечатаны выше указанные книги, какую структуру они имеют, какую цель преследовали, кто является их авторами и как характеризуется ашхарабар в языке этих книг. The article presents a study of the first Modern Armenian printed books of the 17th century: “Craft of Numeration” (Marseille, 1675), “Clarification of David Prophet’s Spiritual Psalms” (Venice, 1687). “Treasure of Measure, Weight, Number and Currency of the Whole World” (Amsterdam, 1699). The paper examines in which printing houses and upon which circumstances these books were printed, which structure and goals they have, how the Modern Armenian is characterized in these books.
Keywords: Bibliography; Books; Writing; Paleography